2008
DOI: 10.2174/187152708784936699
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Calpain and Caspase Pathways in Demyelination and Neurodegeneration in Animal Model of Multiple Sclerosis

Abstract: Experimental autoimmune encephalomyelitis (EAE), a widely recognized animal model of multiple sclerosis (MS), is highly useful for studying inflammation, demyelination, and neurodegeneration in the central nervous system (CNS). EAE exhibits many similarities with MS, which is a chronic inflammatory disease affecting CNS white matter in humans. Various studies have indicated that EAE is a particularly useful animal model for understanding both the mechanisms of immune-mediated CNS pathology and also the progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…30 Calpains are implicated in the demyelination associated with multiple sclerosis, and calpain inhibitors protect the white matter in animal models of this disorder. 31,32 Thus, the white matter sparing observed with LVCapn1-shRNA is thought to reflect protection of oligodendrocytes after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…30 Calpains are implicated in the demyelination associated with multiple sclerosis, and calpain inhibitors protect the white matter in animal models of this disorder. 31,32 Thus, the white matter sparing observed with LVCapn1-shRNA is thought to reflect protection of oligodendrocytes after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, recent studies have shown that in an animal model of multiple sclerosis the activation of caspase-and calpain-mediated pathways contributed to apoptotic death of oligodendrocytes and neurons, promoting the pathological events leading to neurological deficits. Apoptosis is also involved in the disease-regulating as well as in the disease-promoting processes in experimental autoimmune encephalomyelitis (EAE) [12], a widely recognized animal model of multiple sclerosis [14]. Apoptotic cell death occurs in the course of HD, a devastating neurodegenerative disorder caused by a mutation of huntingtin, which is crucial for normal development and may be regarded as a cell survival gene, whereas mutant huntingtin results in neuronal death [15].…”
Section: Neurodegenerative Disorders and Cell Deathmentioning
confidence: 99%
“…Since plasma VEGF is significantly increased in InfEPO mice this does not seem plausible in this experimental model. Calpain activity can be induced by both hypoxia and inflammatory conditions (47, 48) and thus blocking this pathway directly may be more promising as adjunct therapy against CM.…”
Section: Discussionmentioning
confidence: 99%